The prospective relationship between child personality and perceived parenting: Mediation by parental sense of competence. (April 2015) - Egberts, Marthe R.; Prinzie, Peter; Deković, Maja; de Haan, Amaranta D.; van den Akker, Alithe L.
Highlights: We examine child personality as a determinant of perceived parenting. We include three dimensions: parental warmth, overreactivity, psychological control. Child personality relates to all three parenting dimensions in adolescence. For conscientiousness, parental sense of competence mediates this relationship. Abstract: This study examined the prospective relationship between childhood Big Five personality characteristics and perceived parenting in adolescence. In addition, we investigated whether this relationship was mediated by parental sense of competence, and whether associations were different for mothers and fathers. For 274 children, teachers reported on children's Big Five personality characteristics at Time 1, mothers and fathers reported on their sense of competence at Time 2, and the children (who had now become adolescents) rated their parents' warmth, overreactivity and psychological control at Time 3. Mediation analysis revealed both direct and indirect effects. No differences in associations were found for perceived parenting of mothers and fathers. This study demonstrates that child personality in late childhood is significantly related to perceived parental warmth, overreactivity and psychological control in adolescence. In addition, parental sense of competence mediates the relationship between child conscientiousness and perceived parental warmth, overreactivity and psychological control.